Brendan Kennelly’s Cromwell: black comedy as exorcism. Cromwell, de Brendan Kennelly: el humor negro como exorcismo - Villacañas, Beatriz (Estudios Ingleses de la Universidad Complutense, 2003)
This article analyses how the nightmare of Irish history becomes black comedy, de- sentimentalised and thus all the more intense. We shall see Cromwell as poetry dealing
Keywords: Cromwell; Brendan Kennelly; Ireland; Black comedy; Exorcism